Investigation & analysis of Electrical Discharge Machining on Titanium Diboride Ceramic material with various Electrode materials and dielectric fluids - Karthik S; Sivakumar Annamalai (Materials Research Express)
Titanium Diboride is a highly used material in aerospace industry due of its remarkable longevity. Its strength poses a problem to traditional machining methods. This work aims to compare two different dielectric fluids and four different electrode materials to improve EDM process parameters in TiB _2 material. The input parameters were adjusted to find the optimal combination. By studying the fluctuations of output parameters such as MRR, TWR, SR and overcut when processing titanium diboride, researchers can gain valuable insights. This is achieved through experimental studies and the results are then verified using a theoretical regression model. Experimental results confirmed that discharge current, voltage and T _on had a remarkable influence on MRR, TWR and surface roughness in TiB _2 material. It has been observed that tool wear rate when using kerosene-based dielectric fluids is higher than that of deionized water-based dielectric fluids. Tungsten copper electrodes cause slightly less tool wear than tungsten electrodes, and produce higher MRR overall, when compared to other three electrode materials. Using deionized water as a dielectric fluid and a copper as an electrode material can help to obtain a smoother surface. When deionized water is used as a dielectric fluid with tungsten electrodes, the overcut value drops dramatically. Brass electrodes produce a higher overcut value compared to the other three electrode materials. The microstructure of the EDM hole was distinguished by SEM analysis, and the material composition of TIB _2 was determined by EDS analysis.